Management Difficulties of Cerebeller Haemangioblastoma: A Case Report and Literature Review - Chowdhury, Forhad Hossain; Haque, Md Raziul; Islam, Md Shafiqul; Sarkar, Mainul Haque; Alam, Syed Mahbubul (Journal of Medicine, 2010)
The surgical removal of solid deep-seated haemangioblastomas remains challenging, because treatment of these lesions is often complicated by severe bleeding associated with the rich vascularity of this tumor and by severe neural tissue injury associated with the difficulty of en bloc resection. A 55 year-old man, was admitted to us with inability to stand & walk due to imbalance and altered level of conciousness .He has family history of Von Hippel Lindau(VHL) disease. He underwent microsurgery followed by gamma knife radiosurgery 13 years back for cerebeller haemangioblastoma. Magnetic resonance imaging (MRI) revealed intra-axial mass with multiple large cysts in cerebellum with severe compression on cerebellum and brainstem. Preoperative angiography revealed a hypervascular tumor in the posterior fossa, he underwent microsurgery through the previous midline suboccipital craniotomy involving the removal of the arch of C-1. Patient recovered slowly in post operative period. Keywords: Cerebeller haemangioblastoma; Von Hippel Lindau disease; Radiosurgery; Microsurgery DOI: 10.3329/jom.v11i2.5463 J MEDICINE 2010; 11 : 155-158